2005
DOI: 10.1212/01.wnl.0000173061.12776.1f
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome of primary progressive MS: Predictive value of clinical and MRI data

Abstract: The authors sought to identify clinical and MRI predictors of outcome in primary progressive multiple sclerosis (PPMS). Clinical and MRI assessments were performed at baseline and 2 and 5 years (clinical only). At baseline, disease duration, expanded disability status scale (EDSS) and brain volume predicted outcome. Adding short-term change variables, baseline EDSS, changes in T2* lesion load and cord area, and number of new lesions were predictive. Clinical and MRI variables predict long-term outcome in PPMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 11 publications
3
41
1
5
Order By: Relevance
“…They confirmed the limited correlations between clinical manifestations and T2 burden of disease and revealed an important plateauing relationship between T2 burden of disease and disability for EDSS values greater than 4.5 [29]. This observation may contribute to explain why better correlations are found earlier in the disease course and may be a reflection of the fact that once a threshold of T2 lesion volume has been reached, further increases in lesion volume are counterbalanced by brain volume loss and atrophy resulting from tissue contraction [27].…”
Section: Mri To Predict and Monitor Disease Course In The Progressivesupporting
confidence: 65%
See 1 more Smart Citation
“…They confirmed the limited correlations between clinical manifestations and T2 burden of disease and revealed an important plateauing relationship between T2 burden of disease and disability for EDSS values greater than 4.5 [29]. This observation may contribute to explain why better correlations are found earlier in the disease course and may be a reflection of the fact that once a threshold of T2 lesion volume has been reached, further increases in lesion volume are counterbalanced by brain volume loss and atrophy resulting from tissue contraction [27].…”
Section: Mri To Predict and Monitor Disease Course In The Progressivesupporting
confidence: 65%
“…Cross sectional and longitudinal studies in the progressive forms of MS have shown very weak correlations between lesion burden on brain T2 scas and disability [27]. Reasons for the limited correlations include the topography of the lesions, the unspecific nature of T2 lesions, damage of normal appearing brain tissue, limitations of the EDSS scale, limited follow-up, and the potential for neuroplasticity of the remaining healthy tissue, among others [28].…”
Section: Mri To Predict and Monitor Disease Course In The Progressivementioning
confidence: 99%
“…In addition, grey matter atrophy has been shown to be an early feature of PPMS, and may be predictive of clinical course [74,76,78].…”
Section: Imaging Findings In Ppmsmentioning
confidence: 99%
“…7,8 This discrepancy may be explained by several factors, such as differing sample sizes, follow-up periods, and methods used to measure the cord CSA. 7,[13][14][15] Although some cross-sectional studies 11,12 have demonstrated the value of spinal cord atrophy as an independent predictor of clinical outcome, only a few longitudinal studies 9,16,17 have specifically focused on analyzing the clinical relevance of this finding in MS patients, and these include a short follow-up or were not focused on PPMS.…”
Section: Introductionmentioning
confidence: 99%